Auslegung der Spanischen Verfassung, Staat der Autonomen Regionen und Verfassungsgericht - Torres Muro, Ignacio (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2019)
In this essay we provide with an analysis of the autonomy principle based on Constitutional Case Law.
Keywords: Constitutional Court; Autonomous Communities State; Constitutional Interpretation